2015
DOI: 10.1016/j.micinf.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Prelude to oral microbes and chronic diseases: past, present and future

Abstract: Associations between oral and systemic health are ancient. Oral opportunistic bacteria, particularly, Porphyromonas gingivalis and Fusobacterium nucleatum, have recently been deviated from their traditional roles and arguably ascended to central players based on their participations in complex co-dependent mechanisms of diverse systemic chronic diseases risk and pathogenesis, including cancers, rheumatoid-arthritis, and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 71 publications
(159 reference statements)
1
77
0
3
Order By: Relevance
“…NDKs are small (~11–18 kDa), mainly cytoplasmic proteins, usually forming polymers (tetra- or hexamers) and having no known signal leader sequence, thus currently are unassigned to a specific secretion pathway234. The significance of NDK, including the human NDK species, encoded by the nm23 gene, has been suggested for the pathogenesis of several different forms of severe chronic diseases, including cancers567. In breast and other cancer types, the secretion of NDK from cancer cells has been shown to be critical for increased metastatic activity89.…”
mentioning
confidence: 99%
“…NDKs are small (~11–18 kDa), mainly cytoplasmic proteins, usually forming polymers (tetra- or hexamers) and having no known signal leader sequence, thus currently are unassigned to a specific secretion pathway234. The significance of NDK, including the human NDK species, encoded by the nm23 gene, has been suggested for the pathogenesis of several different forms of severe chronic diseases, including cancers567. In breast and other cancer types, the secretion of NDK from cancer cells has been shown to be critical for increased metastatic activity89.…”
mentioning
confidence: 99%
“…This strongly suggests that in the healthy oral state, there is a large variety of yet-to-be-cultured bacteria unlike the bacterial consortium of individuals with changing (declining) oral health. In fact, studies have shown that some bacteria associated with health are poorly known, and include members of TM7 phylum, a bacterial group which does not have a single member cultured in the laboratory but which appears to be widely present in the oral cavity [12]. These data underscore the need to develop culture techniques that improve recovery of bacteria of a healthy human mouth while indicating that disturbed or oral disease mouths are replete of cultivable members.…”
Section: Discussionmentioning
confidence: 99%
“…How these community alterations play out in several diseases of the mouth, especially those involving mixed flora or a cascade of factors triggered by microbial or other signals, is poorly understood. The recent discovery of a novel bacterial co-prevalence pattern in dental carries -a supposedly previously well-characterized disease illustrates the dynamics of this phenomenon [12]. On the other hand, microbiome fingerprints in healthy persons are being examined for potential use in identity based on individuals' unique body microbes [13].…”
Section: Introductionmentioning
confidence: 99%
“…A szájüregi flóra betegségekkel való összefüggése ismert, ám a mindennaposnak tűnő gondolat [7] jelentőségéhez képest mégis kevés figyelmet kap a modern medicinában. A normális flóra változatos előfordulási gyakorisággal, több száz különböző baktériumfajt tartalmaz [8][9][10], amelyek a szájüreg különböző pontjain és a fogak felszí-nén lévő biofilmben eltérő mértékben képesek megtelepedni.…”
Section: Megbeszélésunclassified